Shear performance and degradation mechanism of UHPC-NC interface under composite salts freeze-thaw cycles - Yu, Xiang; Yang, Jun; Zhang, Zhongya; Leng, Jingchen; Chen, Rui; Zhou, Jianting; Zou, Yang (Case Studies in Construction Materials, 2025)
The durability degradation of concrete structures was significant under the actions of salt erosion and freeze-thaw cycle. Interface durability was a key factor affecting the bonding performance between normal concrete (NC) and ultra-high performance concrete (UHPC). In this study, interfacial shear tests of NC structures strengthened by UHPC under composite salt freeze-thaw were carried out. The experimental parameters included different erosive solutions (water, a composite salts of chloride, bicarbonate and sulfate, chloride salt), UHPC types (general UHPC, coarse aggregate UHPC, low-shrinkage UHPC), and interface treatment methods (chiseling, chiseling + planting rebar). Based on the digital image correlation (DIC) technique, the interfacial shear performance under different solution conditions at different periods of freeze-thaw was analyzed. Results show that there were a large number of pores in the UHPC-NC interface under the composite salts freeze-thaw and its microstructure was the sparsest, which caused the most serious damage to the interface. After 10 times of freeze-thaw cycles, the interfacial shear strengths of the specimens subjected to freeze-thaw in water, composite salts and chloride salt, were decreased by 57.3 %, 67.8 %, and 53.5 % respectively, when compared with the specimens without freeze-thaw. Throughout the freeze-thaw cycle regimen, the highest shear strength was witnessed at the interface between coarse aggregate UHPC and NC, reaching 4.39 MPa to 5.66 MPa. Compared with the general UHPC and low-shrinkage UHPC ones respectively, increments of 7.0 % - 18.9 % and 21.3 % - 29.2 % were witnessed. The interface between low-shrinkage UHPC and NC demonstrated desirable stability. After 100 freeze-thaw cycles, the interfacial shear strength only decreased by 17.4 %. By comparing the results of different interface treatments, it was found that as the number of freeze-thaw cycles increased, the effect of planting rebar on suppressing the interface deterioration became increasingly remarkable. During the 0–30 freeze-thaw cycles, compared with the interface specimens with only chiseled surfaces, the shear strength of the interface specimens with planted rebar was increased from 24.2 % to 99.3 %.